PERSEPSI GURU TERHADAP PENERAPAN PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA MELALUI ANALISIS SWOT DI SD NEGERI 2 MATA IE KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR - Onida Damtarina; Nurmasyitah; Aida Fitri (STKIP Subang, 2026)
Differentiated learning is one approach in the Independent Curriculum that aims to accommodate the diversity of students' learning needs. The success of its implementation is influenced by the perceptions of teachers as the main implementers of learning. This study aims to describe teachers' perceptions of the implementation of differentiated learning in the Independent Curriculum through a SWOT analysis at SD Negeri 2 Mata Ie, Darul Imarah District, Aceh Besar Regency. The study used a phenomenological approach with a descriptive qualitative research type. The research subjects consisted of 12 class teachers. Data were obtained through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that teachers have a positive perception of the implementation of differentiated learning because it is considered able to accommodate differences in student learning readiness, interests, and learning profiles, thus making learning more effective and meaningful. The SWOT analysis showed that the strengths of the implementation of differentiated learning lie in the implementation of diagnostic assessments, the application of differentiation of content, process, and product, and the use of varied learning strategies. Weaknesses that are still faced include mapping dynamic learning needs, limited time in developing teaching materials, and implementing differentiated assessments. Opportunities are supported by the Independent Curriculum policy, the Independent Teaching Platform, training, KKG (Teacher Working Group), and the availability of digital learning resources. While threats stem from time constraints, diverse student populations, and inadequate facilities and infrastructure. Thus, the implementation of differentiated learning has been successful, but it still requires strengthening in planning, implementation, and facility support.